Faktor – factor yang Berhubungan dengan Kepuasan Keluarga Pasien di Instalasi Gawat Darurat Rumah Sakit Panti Rapih Yogyakarta - Sugiyatmi, Yohana; Marti, Eva; Oktri Hastuti, Sri (STIKes Panti Rapih, 2021)
ABSTRACT Background : Patient satisfaction is a feeling of pleasure or satisfaction that the services received have met or exceeded the patient's expectations (Nursalam, 2016). Emergency Room (ER) is a part that serves patients with emergency conditions, the action must be effective and efficient according to the quality of service. Satisfaction of patients and their families needs to be measured to improve the quality of services in the Emergency Room Purpose : This study aims to find out relations between the factors related to family satisfaction of patients in the Emergency Room at Panti Rapih Hospital, Yogyakarta. Methods : This research is a quantitative study with a correlational descriptive method using a cross sectional approach. The instrument used was the Patient satisfaction questionnaire format 10 compiled by the previous researcher and the questionnaire about factors related to satisfaction compiled by the researcher. The sample in this study used a non probability sampling with accidental sampling method. The number of respondents is 75 people. The study was conducted on January 13, 2021 to January 28, 2021, Univariate analysis using percentage analysis and bivariate analysis using Spearman correlation to determine the factors associated with satisfaction. Result :There is a significant positive relationship between performance factors and patient family satisfaction (p value = 0.000) rho value = 0.533, there is a significant positive relationship between the facility factor and patient family satisfaction (p value = 0.000) rho value = 0.474, there is a significant positive relationship between service factors and patient family satisfaction (p value = 0.000) rho value = 0.550, there is a significant positive relationship between communication factors and patient family satisfaction (p value = 0.000) rho value = 0.471, there is a significant positive relationship between the atmosphere factor and patient's family satisfaction (p value = 0.000) rho value = 0.513, there is a significant positive relationship between the location factor and patient's family satisfaction (p value = 0.000) rho value = 0474, there is a significant positive relationship between visual design and patient family satisfaction ( p value = 0.000) rho value = 0.435. Conclusion : There is a significant, positive relationship between performance factors, facilities, services, communication, atmosphere, location and visual design on the patient's family satisfaction. This research can be used as a reference in an effort to increase patient and family satisfaction in the hospital.